Preliminary molecular work on sea urchin diadema setosum obtained from Pulau Satang, Sarawak and Pulau Bidong, Terengganu - Noor Liyana, Binti Osman (Universiti Malaysia Sarawak, UNIMAS, 2012)
Sea urchin (Diadema setosum) locally known as ‘Landak Laut’ is characterized by long, black spines, orange ring around the anus and mouth called Aristotle lantern. They can be easily found in coral reef areas around Malaysia coastal waters. They are gardeners of the reef where they feed on algae and help in maintaining the algae from overpopulating the reef, thus making them an important member of complex food web in marine ecosystem. Recently, studies on sea urchins cover diversity, reproduction, anatomical and aquaculture potential. However, in Malaysia, the molecular study on sea urchin is still lacking, therefore this study is designed to carry out preliminary molecular work on sea urchin samples obtained from Pulau Satang, Sarawak and Pulau Bidong, Terengganu. A total of 4 samples from Pulau Satang and 6 samples from Pulau Bidong had been subjected to Total Genomic DNA Extraction using modified CTAB extraction protocol and amplification of COI and 16S rRNA genes. DNA extraction of sea urchin Trg 1 to Trg 5 and Stg A to Stg were successful using modified CTAB protocol. However, amplification of COI gene and 16S rRNA genes had shown negative result, although optimization had been carried out accordingly.